THE USE OF PROCESS GENRE TECHNIQUE TO IMPROVE WRITING SKILL - Ferri Hidayad; Ariya Agustin; Muhammadi Iqbal; M. Bambang Purwanto (Language and Education Journal, 2023)
The purpose of this study was to assess how well the process-genre training in the EFL writing course worked. It also examined the rhetorical strategies and devices authors employed in their essay. The effectiveness of the intervention was also assessed based on how the kids felt about it. It was limited to eighth grade at SMP N 2 Sungai Lilin. This was accomplished by using a quasi-experimental method. The study's experimental group (EG) and control group (CG) were made up of Sections A (N=40) and C (N=39), using the simple random sample approach. The EG was exposed to process-genre intervention while the CG received the conventional writing training. Two research tools were used to collect the data: an interview and a pre-post intervention writing test. The experimental and controlling technique was applied as a result. The eighth-grade English textbook acted as both an EG and CG teaching resource. A paired samples t-test in SPSS 20 was used to compare test results between groups, and an independent samples t-test was performed to compare test outcomes between the two groups at the pre-post-test. Positive changes were made to the students' attitudes toward process-genre writing instruction. EFL teachers need to be capable and skilled when putting the training into their writing classes. Last but not least, it is suggested to do more research by increasing the intervention period to investigate the outcomes of process-genre based writing instruction as an instructional technique in EFL writing classrooms.